A Comprehensive Analysis of Cryptographic Algorithms: Evaluating Security, Efficiency, and Future Challenges - Donagani Ramakrishna; Mohammed Ali Shaik (IEEE Access)
Cryptographic techniques are reviewed in this literature review, with particular attention paid to their applicability, importance, contributions, and field strengths. These algorithms include DES, 3DES, AES, blowfish, two-fish, RC4, one-time pad, RSA, ECC, Diffie-Hellman, MD5, and SHA-256. To analyze the efficiency of these algorithms, a comparative study was conducted using crucial factors, including security, secrecy, and integrity. The assessment also examines known flaws and prospective attacks for each algorithm and highlights current methods and future research gaps. This study provides valuable information on the advantages and disadvantages of different algorithms using a detailed diagram that summarizes the performance outcomes based on secrecy, integrity, and security. In addition, each algorithm’s issues are covered in the review, giving readers a clear grasp of their limitations and possible areas for future research.